SPORT CENTER DI KABUPATEN KUBU RAYA - Dewi, Arisaskia Mahardika; Khaliesh, Hamdil; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Sports are essential activities that play a vital role in improving public health, fitness, and overall well-being. However, Indonesia’s national fitness level remains relatively low due to the limited and uneven distribution of sports facilities across regions. Kubu Raya Regency in West Kalimantan shows an increasing need for adequate sports facilities, in line with population growth, rising athletic achievements, and the active role of local sports organizations. Moreover, the absence of a central public space causes the community to lack an accessible area for interaction and shared activities. In response, the design of a Type B Sport Center in Kubu Raya aims to accommodate various activities such as competitions, training, and recreation while also serving as an open public space that supports social interaction and local economic growth. Using the public open space function approach, the Sport Center is designed to be open, easily accessible, and complemented by recreational areas such as pedestrian paths, gardens, and commercial zones. Its dynamic architectural form creates visual appeal and interactive spatial experiences without disrupting its primary sports function. This design applies John Christopher Jones’s five design stages—idea, information, analysis, synthesis, and evaluation—ensuring a systematic and contextual process. The Sport Center is expected to become a strategic facility that strengthens regional identity and enhances social connectivity in Kubu Raya.